Evaluation of cases with cerebral thrombosis in children - (:unkn) unknown (AVES, 2016)
Aim: We aimed to evaluate the patients who were followed up in our clinic with a diagnosis of cerebral sinovenous thrombosis in terms of age, sex, clinical findings, etiology, thrombophilic factors, imaging findings, treatment and prognosis. Material and Methods: The files of 11 patients who were followed up in our pediatric neurology clinic with a diagnosis of cerebral thrombosis between 1 December 2010 and 31 December 2014 were retrospectively analyzed. Results: Seven of 11 patients were male (63.6%). The median age was 14 years (2-17 years). Six (54%) of the patients presented with a complaint of headache. Other complaints at presentation included diplopia (n:3), weakness and difficulty in speaking (n:1) and seizure (n:1). A diagnosis of pseudotumor cerebri was made in eight of the patients (72.7%). In the etiology, mastoiditis was found in three patients, mastoiditis and meningitis were found in combination in one patient, Behcet's disease was found in three patients and head trauma was found in one patient. In 3 patients, only prothrombotic genetic risk factors were present; one patient had deficiency of protein C and S, one patient had deficiency of antithrombin III and one patient had hyperhomosisteinemia in association with vitamin B12 deficiency. 1A homozygous MTFHR A1298C mutation was detected in the patient who had mastoiditis and meningitis and protein S deficiency and lupus anticoagulant were found in another patient who had mastoiditis. All patients received anticoagulant treatment and all patients recovered without neurological sequelae except one. Conclusions: Cerebral sinovenous thrombosis should be considered in patients who present with headache and focal neurological deficits. Appropriate utilization of imaging studies is necessary for the diagnosis. Detailed ear, nose and throat examination should be performed to detect mastoiditis. It is recommended that genetic risk factors should be investigated, because hereditary thrombophilis factors may have a role in children. Behcet's disease which is relatively common in our country should be considered in differential diagnosis.
Keywords: Anticoagulant therapy; cerebral thrombosis; child; ARTERIAL ISCHEMIC-STROKE; VENOUS SINUS THROMBOSIS; SINOVENOUS THROMBOSIS; RISK-FACTORS; CHILDHOOD; THROMBOEMBOLISM; PROGNOSIS; VEIN